Legal implication of necrophilia in Malaysia: a comparative legal analysis - Mohamad Yunus, Mohamad Ismail; Mohamad Hanifa, Shamshina (LexisNexis Malaysia Sdn. Bhd., 2019)
This article on the law of necrophilia argues that human corpses and the laws which govern the use of dead bodies are uniquely positioned to cause precisely these legal discrepancies since the dead body is a quasi-subject before the law. This paper also presents an argument about one of the fundamental reasons that this gap in law exists. Specifically, it is argued that the ambiguous juridical standing of the human corpse in necrophilia cases compounds the sexual monstrousness of the necrophiliac and of necrophiliac acts. In many countries, there are no laws that address the necessary legalities about necrophilia. This legal incapacity hinders the authority to prosecute individuals who are caught having sex with dead bodies. As a result, necrophiliac sex acts are not illegal. The loophole of the law in regard to some countries to protect the dead is deplored in this paper. People who perform necrophilia, not only adds to the sorrow of grieving family members but also infringes other cultural norms and religious beliefs. Thus, the article emphasises that it is long overdue where action needs to be taken to criminalise necrophilia.